Burnout and Its Consequences on Turnover Intention Among Health Information Managers in University College Hospital, Ibadan, and Lagos University Teaching Hospital, Lagos State - Oluwaseyi, Aibinuomo Ayomide; Oluwafemi, Egbinade Joshua; Morounfoluwa, Adesoji; Daramola, Kolawole Tunmise (American Journal of Biology and Natural Sciences, 2025)
Introduction: Burnout among healthcare professionals has become a growing global concern, particularly in low- and middle-income countries where systemic challenges such as understaffing, poor work-life balance, and inadequate support structures are prevalent. Persistent occupational stress not only jeopardizes the mental well-being of healthcare workers but also compromises the quality of care provided to patients and the efficiency of healthcare delivery systems. Objective: This study aimed to assess the prevalence and contributing factors of burnout among healthcare workers, examine its impact on job performance and turnover intention, and explore potential organizational strategies for mitigating burnout and improving workforce retention. Method of Analysis: A cross-sectional descriptive study was conducted among 200 healthcare workers using a structured questionnaire. The instrument assessed three core dimensions of burnout; emotional exhaustion, depersonalization, and reduced personal accomplishment as well as variables related to job satisfaction, absenteeism, and intention to leave. Descriptive statistics were used to summarize the data, and chi-square tests were employed to determine the association between burnout levels and turnover intention. Results: Findings revealed a high prevalence of burnout, with over 58% of respondents reporting emotional exhaustion and more than 60% actively considering leaving their current job. Key contributing factors included overwhelming workload (58.5%), poor work-life balance (57.5%), lack of managerial support (54.5%), and feelings of underappreciation (59.0%). Chi-square analysis showed a statistically significant association (p < 0.05) between high burnout levels and increased turnover intention. Respondents strongly supported interventions such as flexible work schedules (71.5%), better workload distribution (62.5%), access to counseling services (58.0%), and regular recognition of achievements (65.0%) as effective strategies for reducing burnout. Conclusion: The study highlights the pressing need for healthcare institutions to implement comprehensive burnout prevention frameworks. Strategies must focus on addressing systemic stressors, promoting a culture of recognition, and offering mental health support to improve employee satisfaction and retention, thereby enhancing the overall performance and sustainability of the healthcare workforce.